The International and Political Journal: Areas of political reform in Iraq - Eesa, Khalid hameed (The International and Political Journal, 2024)
This research deals with clarifying the areas of political reform, as the research touched on a number of areas of political reform for any political system, especially the model of democratic governance that is currently promoted and emphasized. In the first section, it dealt with the official fields, including the field of constitutional and legal reform, the field of institutional reform, and opening the field either other political freedom. The second section dealt with the fields of semi-official institutions, including the family, educational institutions, and civil society institutions. Finally, the conclusion included the most important conclusions reached by the research.